Combining stated and revealed preferences for valuing organic chicken meat - Adelina Gschwandtner; Jose Eduardo Ribeiro; César L. Revoredo Giha; Michael P. Burton (University of Kent, School of Economics, 2021)
The present paper uses a jont stated preference (SP) and revealed preference (RP) model in order to estimate the willingness to pay (WTP) for the organic attribute among other key environmental attributes in chicken meat. The stated preference model is based on the respondent's choice from hypothetical choice sets in a choice experiment. The revealed preference model is using a comprehensive data-set of scanned supermarket shopping's to model the choice for chicken meat in a similar manner. The attributes in the stated preference model are based on the ranges of the actual levels of attributes found in supermarket and are presented to respondents using a fractional factorial design. The joint SP-RP approach takes advantage of the benefits of both approaches and addresses econometric issues and biases from both. The results show that the two models appear to reflect similar underlying preferences and can be meaningfully combined. Furthermore, the results show that when combining the RP and SP information, the consumers appear to be willing to pay a larger amount for the organic attribute in chicken meat than when the SP and RP approach's are applied separately. The paper contributes to the literature by being the first to estimate the WTP for organic chicken using a joint estimation approach.
Keywords: C25; Q18; Q51; 330; Choice Experiments; Revealed Preferences; Joint Estimation